THE WAY OF TEACHING WIRTSCHAFTSDEUTSCH TO THE ECONOMICS STUDENTS - Adina SĂCARA-ONIŢA; Andra-Teodora PORUMB (Oradea Journal of Business and Economics, 2025)
The paper is organized on three central themes. In the first part, it has as its central point the term Fachsprache in our case Wirtschaftdeutsch, starting from terminology. The second part deals with the premises of learning and teaching the German language for economics students, the necessary conditions being an advanced knowledge of the German language, conditioned by basic knowledge of economics. An important factor of learning foreign languages is the emotional factor; the student’s motivation is decisive. The last part of the paper presents the methodology of teaching the German language for economics students Wirtschaftdeutsch, the teacher being oriented towards business situations, as close as possible to reality, interspersed with dialogues, with terminology exercises; the logical and free thinking of the economics students is called upon.